Analisis Implementasi Strategi Up Selling pada Penjualan Food and Beverage di Envy Restaurant Hotel Holiday Inn Resort Baruna Bali - Adi, I.G.N. Bagus; Andiani, Nyoman Dini (Jurnal Mosaik Hospitaliti, 2025)
The hospitality industry, particularly the Food and Beverage (F&B) sector, is a rapidly expanding global industry. Up-selling is a crucial sales strategy for revenue generation, especially for Envy Restaurant at Holiday Inn Resort Baruna Bali, which targets daily sales of IDR 30-35 million and relies on this strategy during low seasons. However, its implementation is suboptimal due to pramusaji's (server's) limited awareness and inadequate skills. This qualitative study, conducted at Envy Restaurant from February to August 2024, employed in-depth interviews with pramusaji, supervisors, and managers, non-participatory observation, and documentation (sales reports, SOPs). Data analysis followed the Miles & Huberman model (data reduction, data display, conclusion drawing) with triangulation for validity. The findings indicate that while up- selling is a mandatory strategy, its execution is hindered by a lack of continuous training, limited understanding of effective techniques, absence of structured performance evaluation, and inconsistent motivation and communication between staff and management. Menu engineering analysis further identifies "Plowhorses" (high popularity, low profitability) and "Puzzles" (high profitability, low popularity) as key targets for focused up-selling efforts. The study concludes that effective up-selling is vital for Envy Restaurant's revenue, particularly during low seasons, and that addressing these internal constraints through comprehensive training, structured evaluation, and improved communication is crucial to unlock its full potential and achieve sales targets.